Changes of left ventricular remodeling due to increased afterload in patients with essential hypertension. (15th November 2022) - Hamada, Mareomi; Ogimoto, Akiyoshi; Otani, Takashi; Ohshima, Kiyotaka; Kono, Tamami; Watanabe, Yuta; Tasaka, Tatsuro; Ikeda, Shuntaro
Abstract: Background: It is unclear whether afterload mismatch occurs during the initial stage of essential hypertension (EHT). Additionally, critical left ventricular hypertrophy (LVH) between preserved and reduced systolic functions in hypertension is also unclear. Thus, we aimed to clarify these points. Methods: Forty-five normal control subjects (NCS) and 140 EHT patients participated. EHT patients were subdivided into three groups: group I, without LVH ( n = 37); group II, with LVH ( n = 80); and group III, with LVH and LV heart failure (LVHF) ( n = 23). Routine electrocardiographic and echocardiographic parameters, V5R/V6R ratio, relative wall thickness (RWT), LV mass (LVM) index, and peak systolic wall stress (PSWS) were measured. Results: In group I, LV systolic functions were preserved despite the increase of PSWS. In group II, LVH advanced, but LV systolic functions remained normal. A negative T-wave was observed in 69% of group II and 100% of group III. A significant correlation between RWT and LVM index was seen in NCS and groups I and II (r 2 = 0.545, P < 0.0001) but not in group III. Afterload mismatch occurred in group III due to the decrease in V5R/V6R ratio, the increase of LV end-diastolic dimension, and the LV systolic dysfunctions, which are caused by exhaustion of preload reserve. The boundary of the LVM index between groups II and III was approximately 180 g/m 2 . Conclusion: Afterload mismatch did not occur in group I, but it was observed in group III due to the exhaustion of preload reserve. Highlights: Afterload mismatch did not occur in early hypertensives, and occurred in hypertensives with heart failure due to the loss of preload reserve.